2019
DOI: 10.1111/ejss.12865
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption process of polar and nonpolar compounds in a nanopore model of humic substances

Abstract: Humic substances (HSs) as a major part of soil organic matter (SOM) are complex combinations of natural organic matter, which are ubiquitous in the environment and occur predominantly in soils, residues and natural water. They play a crucial role in the fate and behaviour of contaminants in the environment. In this work, an HS nanopore model was based on a structural motif containing polar and nonpolar domains. The polar domain was represented by the carboxyl groups that predominate in the composition of HSs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Our own previous works aimed at QC modeling of complex HS species using mainly the DFT approach. These studies were focused on typical features of SOM, such as polar functional groups (e.g., carboxyl), nonpolar domains, hydrogen bonding, pH effects, the role of cations and water bridges in the formation of supramolecular structures of SOM, and interactions with small organic molecules such as naphthalene (Aquino et al, 2009(Aquino et al, , 2014Aquino, Tunega, Pasalic et al 2011;Aquino, Tuniga, Schaumann et al, 2011;Kunhi Mouvenchery et al, 2013;Schaumann & Bertmer, 2008;Tunega et al, 2014Tunega et al, , 2020.…”
Section: Modeling Of Som Its Interactions In Soils and Associated Cha...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our own previous works aimed at QC modeling of complex HS species using mainly the DFT approach. These studies were focused on typical features of SOM, such as polar functional groups (e.g., carboxyl), nonpolar domains, hydrogen bonding, pH effects, the role of cations and water bridges in the formation of supramolecular structures of SOM, and interactions with small organic molecules such as naphthalene (Aquino et al, 2009(Aquino et al, , 2014Aquino, Tunega, Pasalic et al 2011;Aquino, Tuniga, Schaumann et al, 2011;Kunhi Mouvenchery et al, 2013;Schaumann & Bertmer, 2008;Tunega et al, 2014Tunega et al, , 2020.…”
Section: Modeling Of Som Its Interactions In Soils and Associated Cha...mentioning
confidence: 99%
“…These studies were focused on typical features of SOM, such as polar functional groups (e.g., carboxyl), nonpolar domains, hydrogen bonding, pH effects, the role of cations and water bridges in the formation of supramolecular structures of SOM, and interactions with small organic molecules such as naphthalene (Aquino et al., 2009, 2014; Aquino, Tunega, Pasalic et al. 2011; Aquino, Tuniga, Schaumann et al., 2011; Kunhi Mouvenchery et al., 2013; Schaumann & Bertmer, 2008; Tunega et al., 2014, 2020). The models used in these investigations spanned from small models representing polar functional groups to larger fragment species such as fatty acid chains to model hydrophillic/hydrophobic domains typical for SOM (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds can be said to be nonpolar compounds if they have bonds between atoms with an attractive ability to gain electrons together, resulting in a distant state where the electrons are shared equally. Meanwhile, if a compound has one atom capable of attracting electrons stronger than other atoms and the electrons from the bond will not be used together equally, then the compound is called a polar compound (Tunega et al 2020). These results are similar to those of (Azka and Abdullah 2012), who showed that the secondary metabolites of water clover ferns Marsilea crenata most of them also dissolved in polar solvents with the yield of methanol extract of 11.98%, ethyl acetate extract of 1.37%, and chloroform extract of 0.31%.…”
Section: Secondary Metabolite Extractionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations allow us to study the dynamics of these models as well as their molecular interactions with proteins. 12 , 13 , 14 , 15 , 16 Computational analysis of such complex systems is opposed by challenges arising from the size of the proteins and the description of their interactions with SOM through force fields. Most proteins active in soil are large, require co‐factors, and/or form complexes with other proteins.…”
Section: Introductionmentioning
confidence: 99%